Pain Relief Without Opioids? Revisiting Naltrexone in Low Doses for Chronic Pain - Pietruszka, Wiktoria; Klasicki , Przemysław; Możarowski , Wiktor; Mozer, Maciej; Pałuchowski , Michał; Mateńko , Jan; Krupa, Agata; Kiełbratowska , Julia; Potrykus, Maria; Krawczyk , Anna (Quality in Sport, 2025)
Introduction and purpose: Chronic pain remains a major clinical challenge, often resistant to conventional therapies and significantly impairing quality of life. As the opioid crisis persists and standard treatments prove insufficient, many patients turn to off-label alternatives. One such candidate is low-dose naltrexone (LDN) – an opioid receptor antagonist traditionally used in addiction therapy, now gaining attention for its unexpected role in pain management. Evidence suggests that LDN may exert anti-inflammatory and immunomodulatory effects beyond opioid receptor antagonism. This review aims to summarize the current understanding of LDN’s clinical use in managing chronic pain, with a focus on conditions such as fibromyalgia (FM), complex regional pain syndrome (CRPS), multiple sclerosis (MS), inflammatory bowel diseases (particularly Crohn’s disease), diabetic neuropathy, and chronic low back pain. Methods: A literature review was conducted using PubMed and Google Scholar, with keywords: “low dose naltrexone,” “LDN,” “chronic pain,” “fibromyalgia,” “multiple sclerosis,” “inflammatory bowel disease,” “CRPS,” “diabetic neuropathy,” and “low back pain.” Brief description and state of knowledge: At doses of 1–5 mg, LDN transiently blocks opioid receptors, enhancing endorphin release, while also modulating microglial activity. This dual mechanism reduces central sensitization and the release of pro-inflammatory cytokines, contributing to pain relief. Conclusion: Though still underrecognized in conventional medicine, LDN shows promise as a safe, low-cost, and potentially paradigm-shifting adjunct in chronic pain management. Its impact on pain, fatigue, mood, and quality of life across multiple conditions merits further high-quality research to validate its role and optimize dosing.